Generation Y’s Work Value in the Malaysian Health Care Equipment Retailing Industry - Zhang, Jun (2012)
The world is changing. A new source of competitiveness has moved into the rival that is PEOPLE! Researchers have shown that organizations have never stopped facing various challenges from human capital and among all the challenges, recruitment and retention are the two biggest concerns (Vedior, 2008) (Appendix 1). One school of thought argued that organizations should never ignore the generational differences while managing their human resource, as they believe that there is no such thing called ‘one-size-fits-all’ and people vary from generation to generation (Henderson and Thompson, 2009; Cennamo and Gardner, 2008; White, 2006). Playing the major role of the workforce throughout the world, including Malaysia, Generation Y has become a hot topic and numerous researchers have been done about their values at work. However, are these assumptions true and universally accepted? Are the work values remaining static within the same generation? Can one ‘one-size-fits-all’ be applied across Gen Y? This research aims to find out the answer!